2010
DOI: 10.1302/0301-620x.92b4.22973
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of early and delayed arthroscopically-assisted reconstruction of the anterior cruciate ligament using hamstring autograft

Abstract: Delayed rather than early reconstruction of the anterior cruciate ligament is the current recommended treatment for injury to this ligament since it is thought to give a better functional outcome. We randomised 105 consecutive patients with injury associated with chondral lesions no more severe than grades 1 and 2 and/or meniscal tears which only required trimming, to early (< two weeks) or delayed (> four to six weeks) reconstruction of the anterior cruciate ligament using a quadrupled hamstring graft. All op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 34 publications
(42 reference statements)
4
78
0
1
Order By: Relevance
“…Further this is not a comparative study with and without thromboprophylaxis. However, if we look at a study published earlier9 and compare it with the present study, one can see that despite not receiving thromboprophylaxis there is not much difference in the incidence of DVT. Prospective randomized clinical trials with and without thromboprophylaxis for arthroscopic assisted ACL reconstruction are required to assess the risk benefit of the use of DVT prophylaxis in these subset of patients.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Further this is not a comparative study with and without thromboprophylaxis. However, if we look at a study published earlier9 and compare it with the present study, one can see that despite not receiving thromboprophylaxis there is not much difference in the incidence of DVT. Prospective randomized clinical trials with and without thromboprophylaxis for arthroscopic assisted ACL reconstruction are required to assess the risk benefit of the use of DVT prophylaxis in these subset of patients.…”
Section: Discussionmentioning
confidence: 66%
“…To the best of our knowledge this is the only study in literature which has focused on incidence of DVT following ACL reconstruction in a prospective fashion. In one of the earlier studies published9 authors compared the outcome of early versus delayed surgery, in which a single dose of Fondapaurinaux (LMWH) was used in the post operative period and no patient had any evidence of DVT. These studies were performed at the same institution at two different points in time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have not reported significant differences in objective and subjective clinical outcomes between early (<2 weeks) versus late ACL reconstruction (>4–12 weeks),30 most recent recommendations, based on moderate quality evidence, support surgery timing at 3 weeks to 5 months after injury 5. Surgery within this period is associated with improved objective knee stability, higher activity level and better knee function when compared with reconstruction after 5 months 10 23 31.…”
Section: Acl Reconstruction: Current State Of the Artmentioning
confidence: 99%
“…However, 2 recent randomized control trials of acute (< 2 weeks) versus delayed ACL reconstruction with hamstring tendon autograft showed no difference in postoperative ROM or functional outcome at any time point. 22,23 We do not routinely delay surgical intervention in patients with acute ACL injuries; however, we do encourage formal physiotherapy focused on regaining full extension and active quadriceps function while patients are awaiting surgery.…”
Section: Timing Of Surgerymentioning
confidence: 99%